2022
DOI: 10.1093/cdn/nzac053.048
|View full text |Cite
|
Sign up to set email alerts
|

A Specific Broccoli Sprout Preparation Reduces Chemically-Induced Colitis Via Gut Microbiota

Abstract: Objectives Sulforaphane is a bioactive metabolite with anti-inflammatory activity that is derived from glucosinolates, which are highly abundant in cruciferous vegetables including broccoli sprouts. There have been limited studies to investigate a whole foods approach to increase sulforaphane levels with therapeutic effect and reduce inflammation. In the current study, using a mouse model of inflammatory bowel disease, we aimed to investigate the ability of steamed broccoli sprouts to amelior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The sprouts were then crushed by mortar and pestle into a fine powder and mixed with purified 5LOD rodent diet powder and water to a concentration of 10% by weight. Our labs have assessed the effects of different diet preparations and the percentage of broccoli sprouts, and found that 5-10% broccoli sprouts by weight reliably produces consistent anti-inflammatory results (98). Diet pellets were formed using a silicone mold to ensure consistent sizing, and allowed to dry at room temperature for up to 48 hours in a chemical safety hood to facilitate moisture evaporation, and after drying were stored in ziploc bags in a −10°C freezer until future use.…”
Section: Methodsmentioning
confidence: 99%
“…The sprouts were then crushed by mortar and pestle into a fine powder and mixed with purified 5LOD rodent diet powder and water to a concentration of 10% by weight. Our labs have assessed the effects of different diet preparations and the percentage of broccoli sprouts, and found that 5-10% broccoli sprouts by weight reliably produces consistent anti-inflammatory results (98). Diet pellets were formed using a silicone mold to ensure consistent sizing, and allowed to dry at room temperature for up to 48 hours in a chemical safety hood to facilitate moisture evaporation, and after drying were stored in ziploc bags in a −10°C freezer until future use.…”
Section: Methodsmentioning
confidence: 99%
“…A steamed broccoli sprouts diet inhibited TNFɑ, IL1β, and IL6 and promoted bacteria richness such as Bacillota (formerly Firmicutes), Pseudomonadota (formerly Proteobacteria), Bacteroides, and Verrucomicrobiota against dysbiosis and IBD in DSS mice [ 48 ]. Microbial hydrolases and commensal microbiota promoted the beneficial effects of SFN [ 144 ] and SCFA production and decreased colonic ulceration [ 105 ]. Interestingly, eating broccoli sprouts early in life can improve microbiota richness.…”
Section: Discussionmentioning
confidence: 99%
“…The control diet was 100% irradiated 5LOD diet irradiated 5LOD rodent diet powder (ScottPharma Inc., Marlborough, MA, #50795) mixed with ultra-pure water. The freeze-dried sprouts were crushed by mortar and pestle into a fine powder and mixed with the 5LOD powder and water to a concentration of 10% by weight to form the treatment diet, as that concentration reliably produces consistent anti-inflammatory results ( 48 ). Diet pellets were formed using a silicone mold to ensure consistent sizing, dried at room temperature for up to 48 h in a chemical safety hood to facilitate moisture evaporation, and after drying were stored in Ziploc bags in a −10℃ freezer until future use.…”
Section: Methodsmentioning
confidence: 99%
“…Purified GLR or SFN has been demonstrated to protect against chemical-induced ulcerative colitis in mice ( 38 , 47 49 ) and some pathogenic bacteria in the gut ( 50 , 51 ). However, purified SFN is unstable ( 52 , 53 ), and pure GLR induces extremely variable rates of conversion in humans ( 40 , 53 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation